Diversidade genética em copaibeiras e pequizeiros por meio de oligonucleotídeos ISSR - Pedro Vitor de Souza Silva (2024)
The copaiba tree (Copaifera langsdorffii Desf.) and the pequi tree (Caryocar brasiliense Camb.) are prominent tree species in the Brazilian flora, playing relevant roles in tropical ecosystems. The copaiba tree stands out for exuding a resinous oil with medicinal and industrial properties. The pequi tree has its fruits appreciated in regional cuisine, besides pharmaceutical potentialities. Studies of genetic diversity provide support for the development of conservation strategies, sustainable management, and understanding of population dynamics. This study aimed to estimate the genetic diversity among accessions of copaiba and pequi trees in municipalities located in the North and Northwest mesoregions of the state of Minas Gerais, Brazil, using ISSR (Inter Simple Sequences Repeats) oligonucleotides. The Copaiba accessions were obtained in Montes Claros MG and Mirabela-MG, totaling 20 accessions. In turn, the pequi accessions were collected in Bocaiuva-MG, Bonfinópolis-MG, Dom Bosco-MG, and Salinas-MG, totaling 40 accessions. A protocol adapted from the CTAB method for DNA extraction was used, followed by Polymerase Chain Reaction (PCR) reactions using ISSR oligonucleotides from the University of British Columbia collection (UBC primer set #9, Vancouver, Canada), with prior testing of temperature gradients. For the copaiba tree, 16 oligonucleotides were tested, of which 11 showed polymorphisms. In the case of the pequi tree, all 100 oligonucleotides from the collection were tested, and only four manifested polymorphisms, making it impossible to construct viable binary matrices for dissimilarity estimation. For the copaiba tree, molecular data were used to estimate genetic distances among accessions, calculated by the 'Nei and Li' index. These pieces of information were applied in hierarchical clustering and Tocher optimization analyses. The reactions produced 105 fragments used in the generation of the dissimilarity matrix, revealing wide variability among the 20 copaiba accessions (from 19.04% to 75.38%). The estimated discriminatory power of the locus in HOligo was 0.2837, while that of PICOligo was 0.2279. A total of 97 pairs of accessions showed dissimilarity values exceeding 50%. The Cophenetic Correlation Coefficient (CCC) was high, reaching 0.8275 in dendrogram acquisition procedures (stress of 11.92%). The applications of hierarchical clustering and Tocher optimization methods resulted in the separation into three groups, distinguishing accessions 1, 14, and the rest. The results of the pequi tree tests suggest the need for the utilization of other markers for dissimilarity construction. As for the copaiba tree results, they present potential to support the development of conservation strategies.